Physical and Lattice Gas Automata Fluid Flow Modeling in Real Porous Media - Umar Fauzi; Mulyadi Mulyadi; A. S. Bahri (Indonesian Journal of Physics, 2005)
Physical modeling of fluid flow in real porous media was conducted to validate Lattice-gas Automata (LGA) method. Direct observation of fluid flow was carried out on a pond with obstacles in laboratory scale. Velocity patterns of fluid flow were derived using tracer observed from images. A good agreement of velocity pattern was shown in physical and LGA modeling. This method can be used as a validation technique for numerical modeling of complex structure of porous media. The validated LGA method was a then applied to model fluid flow in real rocks. Digital image of real rocks were created from thin sections by means of image processing technique. The rock image was then used as a medium for fluid flow modeling. Investigation of effective porosity, tortuosity, and permeability can be carried out easier with the help of LGA method. Low velocity pattern shown in the model can be interpreted as non-effective porosity, since it does not have any significant contribution to the fluid flow. Effective porosity depends strongly on direction of the fluid flow.